(untitled) (American Journal of Islam and Society, 2006)
In writing Reading Arab Women’s Autobiographies: Shahrazad Tells Her Story, Nawar Al-Hassan Golley’s goal is to fill a critical gap. Recent books like Marilyn Booth’s May Her Likes Be Multiplied: Biography and Gender Politics in Egypt (Berkeley: University of California Press, 2001) analyze women’s relation to biography from Zainab Fawwaz’s Scattered Pearls (1894) onward. However, any critical analysis of Arab women’s autobiography is scarce, if not non-existent. In its efforts to fill this critical gap, Reading Arab Women’s Autobiographies carves out a dual readership. Delineating past and present meanings both within and without Islam of “Arab,” “Arab world,” “hijab,” and “harem” with an eye to the non-Arab reader, Golley’s analysis of five autobiographical texts and three anthologies of women’s collected stories simultaneously participates in a conversation with other Arab women scholars about modes of text production, distribution, and the overall place of women’s autobiography within Arab feminism. Part 1, “Political Theory: Colonial Discourse, Feminist Theory, and Arab Feminism,” contains three chapters: “Why Colonial Discourse?”; “Feminism, Nationalism, and Colonialism in the Arab World”; and “Huda Shaarawi’s Harem Years: The Memoirs of an Egyptian Feminist.” In the first two, the author argues for the inclusion of gender-related issues within colonial discourse analysis and for the necessity of adopting Spivak’s “strategic essentialism” when speaking of “Arab women.” In outlining a brief history of Arab feminism, Golley strives to both demystify the “aura of exoticism” that has surrounded Arab women and to demonstrate that Arab feminism “is not alien to Arab culture.” ...